2006
DOI: 10.1158/1055-9965.epi-06-0465
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Risk of Endometrial Cancer: A Population-Based Prospective Cohort Study

Abstract: Physical activity is involved in the regulation of metabolic and hormonal pathways and is one of the factors important for the maintenance of body weight; obesity is a risk factor for endometrial cancer. A connection between physical activity and endometrial cancer risk through hormonal mechanisms, possibly mediated by body weight, is biologically plausible. Only one study has investigated total physical activity, and no previous study has examined leisure time inactivity directly. We investigated the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 56 publications
12
97
1
1
Order By: Relevance
“…For the review on sedentary behavior and cancer, 18 relevant articles were identified (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). For sedentary behavior and adiposity, 76 articles originating from 62 studies were selected for review (10,12,13,(15)(16)(17).…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the review on sedentary behavior and cancer, 18 relevant articles were identified (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). For sedentary behavior and adiposity, 76 articles originating from 62 studies were selected for review (10,12,13,(15)(16)(17).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Statistically significant, positive associations between sedentary behavior and cancer were found in 8 of the 11 studies (21,23,24,26,29,30,33,35). An additional study had a borderline statistically significant, positive association (25), and one observed a nonstatistically significant risk increase (31).…”
Section: Sedentary Behavior and Cancermentioning
confidence: 95%
See 1 more Smart Citation
“…Other cohort studies have shown differing results; most have found a decreased risk in physically active women (Furberg and Thune, 2003;Schouten et al, 2004;Friberg et al, 2006), whereas others showed no association (Colbert et al, 2003). Hypothesised mechanisms include changes in obesity and/or fat mass as well as a reduced exposure to endogenous oestrogens (McTiernan et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…To date, sedentary behaviour epidemiology has mainly focused on outcomes related to cardiovascular and metabolic health. Measures of sedentary behaviour have however, also been related to gallbladder disease (Leitzmann et al, 1998;Leitzmann et al, 1999), cancer (Friberg et al, 2006;Gierach et al, 2009;Patel et al, 2008;Patel et al, 2006), and mental disorders (Sanchez-Villegas et al, 2008). These relationships with conditions that involve various body systems, suggest a wide-ranging impact of sedentary behaviour on health.…”
Section: Introductionmentioning
confidence: 99%